Pemanfaatan Teknologi Informasi Oleh Lansia Sebagai Penunjang Activity Of Daily Living - Widayanti, Tri; Rahayu, Bety Agustina (PT.Mantaya Idea Batara, 2024)
Activities of daily living are activities carried out routinely by each individual in their daily life. Current technological developments have also been utilized by elderly people in the face of functional decline to support activities related to physical and psychological exercise. This research analyzes the use of technology and information technology in the elderly as supporting activities of daily living. This research is a quantitative descriptive research with a questionnaire instrument. The research was conducted in June 2023 at Posyandu Teratai I Padukuhan Pungkuran Pleret Bantul Yogyakarta using an accidental sampling technique and obtained 24 respondents. Description of the technology used by respondents to support activities of daily living. From the household equipment technology category, the most widely used are rice cookers and refrigerators, 27.08% each, from the health equipment category, such as weight scales and thermometers, 8 each. 33%, in the information and communication technology category the majority use television (46.34%). Only 17% of respondents used YouTube as a guide to exercise for the elderly. The information technology used by the elderly as a source of health information is 3% television, 10% radio, and 6% social media. There are 3 types of barriers to using technology in the elderly, namely because they don't have technology tools (25%), are not used to/difficulty using them (29%), and don't have time to use them (4%). Elderly people in Padukuhan Pungkuran Pleret Bantul Yogyakarta do not make much use of technology and information technology to support activities of daily living.